Health Risk Assessment of Metals in African Aphrodisiacs: A Case Study of Aqueous Concoctions from Johannesburg and Durban Herbal Markets, South Africa - Siphesihle Dube; Nkosinathi Makhubela; Lawrence Mzukisi Madikizela; Nkoana Ishmael Mongalo; Vusumzi Emmanuel Pakade; Bethusile Rejoice Maseko; Somandla Ncube (Applied Sciences, 2023)
Consumption of aphrodisiacs is a common practice in South Africa. Hence, determining the levels of trace metals as potential pollutants is necessary to protect consumers’ health. The current study reports a health risk assessment due to metals in aphrodisiacs collected from herbal markets in Johannesburg and Durban, South Africa. Samples were digested using microwave-assisted digestion followed by inductively coupled plasma-optical emission spectrometry analysis. The results showed that the concentrations of common metals (Na, K, Mg, and Ca) were within the guideline limits for human consumption, while the trace metals (Ni, Cr, Co, As, Cd, and Pb) were above the limits, recording values of 0.132–0.268, 0.209–0.308, 0.224–0.405, 0.0884–0.230, 0.0402–1.11, and 0.146–0.207 mg L−1, respectively. The source of the trace metals was traced to the tap water probably collected from dilapidated buildings where the water systems are ailing. A strong correlation for metals with similar sources was observed, notably for Pb and Cd that leach from water pipes. The aphrodisiacs had low consumption rates, and the health risk assessment gave a hazard quotient of 0.225 as a total for all studied metals. The group of aphrodisiacs investigated in the current study therefore poses minimal health risks and can be consumed without fear of metal contamination. More inclusive studies are, however, needed to have a better understanding of aphrodisiacs with the aim of potentially commercializing them like the other commercialized herbal concoctions currently distributed in South African markets and pharmacies.